1989
DOI: 10.1111/j.1526-4610.1989.hed2902093.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects of Weekend Headache Sufferers in Comparison with Migraine Patients

Abstract: Sometimes the relaxation after stress may trigger a migraine attack. This is the principle that underlies that particular variant of migraine called "weekend headache". We hypothesize the presence in weekend headache prone subjects of a particular psychological background, different from that of common migraine sufferers. In order to detect possible differences supporting our hypothesis, we studied 104 new outpatients: 46 patients suffering from headache only on weekends (23 males and 23 females) and 58 matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…The subjects were tested with the State-Trait Anxiety Inventory (STAI) to rule out both trait and state anxiety. In the Italian population, the normal STAI-S range is 45.2 Ϯ 12.37 for adult women and 40.17 Ϯ 10.01 for men, whereas the STAI-T normal range is 46.1 Ϯ 11.53 for women and 39.53 Ϯ 9.25 for men (Spielberg et al, 1980;Nattero et al, 1989). In our routine clinical experience, these values correspond to a range of ϳ32-52 for the STAI-S and ϳ30 -55 for the STAI-T.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects were tested with the State-Trait Anxiety Inventory (STAI) to rule out both trait and state anxiety. In the Italian population, the normal STAI-S range is 45.2 Ϯ 12.37 for adult women and 40.17 Ϯ 10.01 for men, whereas the STAI-T normal range is 46.1 Ϯ 11.53 for women and 39.53 Ϯ 9.25 for men (Spielberg et al, 1980;Nattero et al, 1989). In our routine clinical experience, these values correspond to a range of ϳ32-52 for the STAI-S and ϳ30 -55 for the STAI-T.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Premonitory features include changes in mood or behavior that precede the onset of an attack. Trigger factors, measurable precipitants associated with an increased probability of an attack, can include stressful events, hormonal changes, weather changes, and certain foods, although some studies demonstrate reduced odds for migraine attacks in relation to certain variables.…”
Section: Objectivementioning
confidence: 99%
“…Trigger factors, measurable precipitants associated with an increased probability of an attack, can include stressful events, hormonal changes, weather changes, and certain foods, although some studies demonstrate reduced odds for migraine attacks in relation to certain variables. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In patient surveys, perceived stress was associated with migraine onset in up to 80% of respondents. [13][14][15][16] Diary studies have shown that "daily hassles" significantly increase in the 2-to 3-day period before a migraine day.…”
mentioning
confidence: 99%
See 2 more Smart Citations